Knowledge ecosystem using corporate taxonomy - Saiyed Yeop, Sharifah Fahimah; Mohd Yusof, Nurhannan; Mustaffa, Maria Hani (Universiti Teknologi MARA, Kedah, 2018)
The proper management of all types of knowledge in the organization is crucial as they are a vital, corporate asset and required to provide evidences of actions and decisions. Data, information and knowledge are become more important in the organization to support accountability and transparency, to comply with legal and regulatory obligations including Data Protection Act and Intellectual Property Act. In the higher learning organization, for example, the records are important to protect the interest of academician, students and other stakeholders. Knowledge ecosystem can be portrayed in the form of knowledge map, as one of the techniques to identify and translate knowledge in the organization. Knowledge of administrative personnel, support staff, management experts, researchers and academician exist in records such as minutes of meeting, memo, financial document, presentation slides, letters, research articles, conference papers and etc. The proper organization of those materials will support the knowledge translation through integration of knowledge map and conceptual framework for understanding many complex processes, resources and people involved in organization. The objective of developing the knowledge ecosystem in organization nowadays, should not only produce standard guidelines in managing files and records, furthermore it should help us to understand how knowledge flows in the organization. The filing structure should be used as a comprehensive tool to understand complex processes, practices, and should be able to trace the nonefficient process flow in the organization.